MANAJEMEN KOLABORATIF GURU PENGGERAK DALAM PENINGKATAN KUALITAS KINERJA GURU - Januar Musa; Silvi Listia Dewi; Alfi Syahrin (Hijri, 2025)
This research aims to analyze the management of teacher mover collaboration in improving the quality of middle school teacher performance in Southeast Aceh Regency using the POAC (Planning, Organizing, Actuating, Controling) method. The approach used in this research is qualitative. Data collection techniques use interviews, observation and interrelated document studies. Data analysis techniques go through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that: Teacher collaboration management is the driving force in improving the quality of performance of State Middle School teachers in Southeast Aceh Regency. The planning is going well, starting with identifying teacher needs, followed by discussions involving all teachers through effective communication and preparation of work programs, but there is still need for improvement in the preparation. vision and mission so that the desired goals are achieved. In the organizing function, it is still necessary to clarify the division of tasks between each element of the collaboration team so that they can be responsible for the success of this function. In its implementation function, collaborative management takes place in the form of collaborative activities and improvements are needed in managing time and lack of funds and infrastructure by strengthening the concept of appreciative inquiry. Likewise, the supervisory function has been carried out well by observing, providing feedback, mentoring and coaching, and conducting evaluation meetings to follow up on the development of collaborative activities with indicators of teacher performance quality increasing from before.